NEGARA DALAM TINJAUAN AL-QUR’AN - Asrori Mukhtarom; Priyo Susilo (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2019)
There are thousands of verses in the Koran, and many verses have been discussing the definition, meaning, purpose, and form of a state. By way this essence, it is clear that the Qur'an also considers the importance of the existence of a state for human being. Furthermore, his fact also states that for people who believe in the Qur‟an must have attention and responsibility for the development of a state. According to the Qur‟an, the term "a state" is common in relation to al-Balad, Baldah, al-Qaryah, al-QurâN, ad-Dâr, and ad-Diyâr. The main purpose or goal of a state, according to the perspective of the Quran, is written and discussed in several surahs and verses as well, for example in surah al-Hadid verse 25, which says that people must always uphold justice. It was also mentioned in surah al-Hajj verse 41which says that a state is a structure, mechanism or guidance for achievement, is a human who lives in this world and in the day after tomorrow. In addition, in the surah Hud verse 61, the Qur'an states that the main purpose and goal of a state is to create public welfare. On the other hand, in relation to the form and system of a state, those two things are not mentioned in the Qur'an in a straight way. However, the Qur‟an only talks about values that can be a basic idea in life as a shared ivilization in society. For example, the value of freedom discussed in sulah al-Baqarah verse 256. This verse tells about the importance of unity as a human being.Especially in surah al-Hujurat verse 10 which tells about making relations as a human in society. In addition, the value of justice is also stated in Surah an-Nisa verse 58. Furthermore, equality is also discussed in surah al-Hujurat verse 13. These values have been applied by our prophet Muhammad PUBH, when he led Medina as a state that had different characteristics and ways of thinking at the time, and finally, he did very well in leading a country